Study on Composition Distribution and Ferromagnetism of Monodisperse FePt Nanoparticles - Xu YM; Li Q; Wang HB; Wang H; Zhang J; Yang FJ (Nanoscale Research Letters, 2010)
Abstract Monodisperse FePt nanoparticles with size of 4.5 and 6.0 nm were prepared by simultaneous reduction of platinum acetylacetonate and thermal decomposition of iron pentacarbonyl in benzylether. The crystallography structure, size, and composition of the FePt nanoparticles were examined by X-ray diffraction and transmission electron microscopy. Energy dispersive X-ray spectrometry measurements of individual particles indicate a broad compositional distribution in both the 4.5 and 6 nm FePt nanoparticles. The effects of compositional distribution on the phase-transition and magnetic properties of the FePt nanoparticles were investigated.